Malacología Latinoamericana. Moluscos de agua dulce de Argentina - Rumi, Alejandra (2008)
A report and an updated list with comments on the species of freshwater molluscs of Argentina which covers an area of 2 777 815 km2is presented. Distributions of Gastropoda and Bivalvia families, endemic, exotic, invasive as well as entities of sanitary importance are also studied and recommendations on their conservation are provided. Molluscs related to the Del Plata Basin have been thoroughly studied in comparison to others areas of the country. This fauna exhibits relatively the biggest specific richness and keeps its affinity with the fauna of other regions of the basin in areas of Paraguay and Brasil. The 4 500 records of molluscs considered in this paper arise from the study of the collections of Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Buenos Aires; Museo de La Plata, La Plata and Fundación “Miguel Lillo”, Tucumán. These institutions keep very important collections of molluscs in southern South America. Field information has recently been obtained and localities cited by other authors are also included in the data base. Until today, 166 species have been described, 101 belonging to 10 families of Gastropoda and 65 to 7 of Bivalvia. Families with highest specific richness are Lithoglyphidae (22) and Sphaeriidae (25), respectively. The number of endemic species (those present only in Argentina) by family is: Gastropoda: Ampullariidae (1), Cochliopidae (10), Lithoglyphidae (11), Thiariidae (3), Chilinidae (11), Lymnaeidae (2) and Physidae (2?); Bivalvia: Hyriidae (1?); Etheriidae (1?) and Sphaeriidae (10). Families with a distribution that comprise almost the whole country are: the Sphaeriidae and the gastropods Cochliopidae, Chilinidae and Lymnaeidae. Families Erodonidae and Solecurtidae (Bivalvia) were registered in mixohaline environments from Buenos Aires province. Gastropod families Thiaridae and Glacidorbiidae show a very restricted distribution. The rest of the families are present mainly in the center and north of the country. Species of sanitary interest are the propagators of: schistosomiasis -Biomphalaria peregrina, B. straminea y B. tenagophila, Planorbidae-, fasciolasis -Lymnaea viatrix and L. columnella, Lymnaeidae- and dermatitis -Chilina gibbosa and C. fluminea, Chilinidae. Invasive species are: Corbicula fluminea (Corbiculidae) and Limnoperna fortunei (Mytilidae).The construction of new areas for the protection and conservation of the high risk endemic species of freshwater molluscs is a priority. It is necessary to give special attention to the species of the patagonic mountain range and of the mesopotamic area of the Del Plata Basin.